Heat transfer enhancement of a modularised thermoelectric power generator for passenger vehicles - Li, Bo; Huang, Kuo; Yan, Yuying; Li, Yong; Twaha, Ssennoga; Zhu, Jie (Elsevier, 2017)
Transport represents over a quarter of Europe's greenhouse gas emissions and is the leading cause of air pollution in cities. It has not seen the same gradual decline in emissions as other sectors. Recently, the thermoelectric power generation (TEG) technology emerges as an alternative solution to the emission reduction challenge in this area. In this paper, we present an innovative pathway to an improved heat supply into the concentric shape-adapted TEG modules, integrating the heat pipe technologies. It relies on a phase changing approach which enhances the heat flux through the TEG surface. In order to improve the heat transfer for higher efficiency, in our work, the heat pipes are configured in the radial direction of the exhaust streams. The analysis shows that the power output is adequate for the limited space under the chassis of the passenger car. Much effort can also be applied to obtain enhanced convective heat transfer by adjusting the heat pipes at the dual sides of the concentric TEG modules. Heat enhancement at the hot side of the TEG has an effective impact on the total power out of the TEG modules. However, such improvements can be offset by the adjustment made from the coolant side. Predictably, the whole temperature profile of TEG system is subject to the durability and operational limitations of each component. Furthermore, the results highlight the importance of heat transfer versus the TEG power generation under two possible configurations in the passenger car. The highest power output per repeat unit is achieved at 29.8 W per 0.45 L with a ZT value 0.87 for a Bi2Te3-based thermoelectric material in our studies. The study provides an insight into a structurally achievable heat exchanger system for other high-temperature thermoelectric materials.